Pemasaran Online Bagi Pelaku Usaha - Sally Maria Bramana; Rini Apriyani; Achmad Johan Musoddiq3 (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The purpose of this service is to provide training for business actors by utilizing technology in online marketing so as to increase sales volume for business actors during the covid-19 pandemic. The results of this community service are 1) providing guidance to business actors 2) Business actors participating in this activity are business actors affected by covid-19 so that this material can help business actors to increase sales volume through online marketing.